Multi-objective Dynamic Expansion Planning of Active Meshed Distribution Network: Sizing, Siting, and Timing of Hub and Voltage Regulators - Oskuee, Mohammad Reza Jannati; Mojtahedzadeh, Shahram; Karimi, Masoumeh (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2022)
Distribution network expansion planning is a technique for managing the system effectively in the face of future challenges. This work investigates the design of a mesh distribution network to allocate substations, DGs, voltage regulators, feeder routing, switch placement, and the integration of multiple energy carrier systems. Dynamic modeling for multi-objective system expansion planning is proposed in this study to identify the optimal plan and operational strategy. The uncertainties related to DGs, electricity, heat load, and their prices are considered in the planning process. A 54-Bus distribution network is applied to evaluate the methodology and discuss the results.